Tematic maps for irrigation of the watermelon crop in Piaui state - de Oliveira, José Roberto; Mousinho, Francisco Edinaldo Pinto; Andrade Júnior, Aderson Soares de; Saraiva, Kleiton Rocha; Nunes, Francisco das Chagas de Andrade Porto (Revista Agrogeoambiental, 2020)
In semi-arid regions, inadequate management of irrigation in watermelon crops greatly increases yield losses. As a result, we sought to regionalize irrigation slides necessary for watermelon cultivation in the State of Piauí, considering different sowing times and soils with different water retention capacities. Irrigation slides were determined by the crop water balance, considering a historical series of fifteen years, originating from daily pluviometric precipitation records in 165 sites of this region. The reference evapotranspiration (ET0) and the respective crude irrigation slides were estimated on a daily scale for each site. Then, the crude irrigation slides were spatialized to the entire target region through a routine performed in Excel and later using the SPRING software, depending on the available water capacity in the soil and the date of sowing. Seeding dates with the need for minor irrigation slides for watermelon cultivation in Piauí were January 1st, February 1st and March 1st and in relation to sowing dates, the largest irrigation slides were verified on August 1st, September 1st and October 1st. Regionalized irrigation sheets varied according to the available water capacity in the soil and date of planting.